2007
DOI: 10.1016/s1472-6483(10)60897-8
|View full text |Cite
|
Sign up to set email alerts
|

Fertility assessment in non-infertile HIV-infected women and their partners

Abstract: The objective of the study was to assess the fertility of non-infertile couples seeking pregnancy in whom the woman was HIV infected. Therefore, a cross-sectional study was conducted between January 1998 and March 2005. A standardized fertility assessment was performed in all the included couples. A total of 130 women and 121 men were evaluated. Their median age was 34 years (range 22-43). Only 7.2% of the women were severely immunocompromised. The majority of women had regular cycles. Only one woman had an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Infected women who have advanced disease (21) or are wasted (15) have an increase in anovulatory cycles. One small study demonstrated a 27.8% incidence of tubal occlusion on hysterosalpingogram among seropositive women (196), but this is not supported elsewhere in the literature. One would expect an increase in tubal factor infertility with HIV infection similar to what has been seen in other groups of women with sexually transmitted infections.…”
Section: Fertilitymentioning
confidence: 85%
“…Infected women who have advanced disease (21) or are wasted (15) have an increase in anovulatory cycles. One small study demonstrated a 27.8% incidence of tubal occlusion on hysterosalpingogram among seropositive women (196), but this is not supported elsewhere in the literature. One would expect an increase in tubal factor infertility with HIV infection similar to what has been seen in other groups of women with sexually transmitted infections.…”
Section: Fertilitymentioning
confidence: 85%
“…Furthermore, the clinical presentation among HIV-infected women with PID may be more severe than in uninfected women [36, 37]. A cross-sectional study from Spain of 130 HIV-infected women undergoing fertility assessment found that almost one-third had evidence of tubal occlusion [38]. Another potential contributing factor to subfertility in HIV-infected women is a possible increase in amenorrhea, oligomenorrhea, and irregular periods, particularly with lower CD4 counts [3942].…”
Section: Rationale For Preconception Carementioning
confidence: 99%
“…Sauer et al reported that ART outcome was not altered in male-HIV couples (13), despite poorer sperm quality (21)(22)(23). Likewise, acceptable pregnancy rates of 23.9% were reported in female-HIV couples (16).…”
mentioning
confidence: 99%